Islamic Religious Education Teachers' Strategies in Implementing Digital-Based Learning - Arief Cahyo Saputro; Muh. Nur. Rochim Maksum (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2026)
This study aims to examine the strategies applied by Islamic Religious Education teachers in implementing digital-based learning at SMA 1 Sukoharjo. This research applies a qualitative method with a case study approach. The research technique includes observation, interviews, and documentation with the research subjects of Islamic Religious Education teachers. The focus of the researcher includes the digital learning strategies applied, the use of technology in learning. The results of the study show that Islamic religious education teachers apply various strategies in digital-based learning, such as the use of digital learning media, the use of online learning platforms, and the development of interactive learning methods that are in line with the characteristics of students. In addition, teachers also play a role in increasing students' learning motivation through innovative and adaptive approaches to technological developments. The implementation of a digital-based learning system has a positive influence on increasing student involvement and understanding.